The short-legged Andean cosmetids revisited: the genus Libitia Simon, 1879 with description of two new species (Opiliones, Cosmetidae) - Medrano, Miguel; Ázara, Ludson Neves de; Kury, Adriano Brilhante (European Journal of Taxonomy, 2020)
The old genus Libitia Simon, 1879 of small Andean harvestmen is revisited. The monotypic genus Libitiella Roewer, 1947 is herein considered a junior subjective synonym of Libitia. Accordingly, Libitiella bipunctata (Sørensen, 1932) is restored to the combination Libitia bipunctata. The species Libitia cordata and Libitia bipunctata comb. nov. are redescribed and the new species Libitia gandalf sp. nov. and Libitia iguaque sp. nov. are herein described from Cordillera Oriental of Colombian Andes (Chingaza Natural Park and Iguaque Natural Park, respectively). The species Gonyleptes multimaculatus Wood 1869, currently under the synonymy of L. cordata, is revalidated and transferred to Paecilaemella Roewer, 1925 forming Paecilaemella multimaculata comb. nov., and the species Cynorta itacoaiensis H. Soares, 1970 is herein considered a junior subjective synonym of it. In addition, the second current species of the genus, Libitia fusca (Simon, 1879), is transferred to Metalibitia. Libitia is diagnosed based in genital and external morphology, an identification key of the four species and distribution maps are offered.